Garranes : an early medieval royal site in south-west Ireland - O'Brien, William, 1961- (Archaeopress Archaeology, 2021)
This title presents the results of an interdisciplinary project (2011-18) where archaeological survey and excavation, supported by specialist studies, examined the early medieval landscape of Garranes. A ringfort in the mid-Cork region of south-west Ireland, this 'royal site' is considered to have been a centre of political power and elite residence.